Exchange rates in Singapore and Malaysia: are they driven by the same fundamentals? - Baharumshah, Ahmad Zubaidi; MacDonald, Ronald; Mohd, Siti Hamizah (Faculty of Economics & Administration, University of Malaya and Malaysian Economic Association, 2010)
This study examines the empirical link between exchange rates and fundamentals using the monetary model of the exchange rate for the Malaysian ringgit and the Singapore dollar against two key bilateral rates-the US dollar and the Japanese yen. We formally tested for the long-run monetary model of exchange rate determination and found several interesting results. First, a unique cointegrating relationship was identified, based on theory and data, which means that monetary variables and the exchange rate are connected. Second, we found that it is the exchange rate that adjusts to the long-run equilibrium after a shock and not the other way round. Finally, it is shown that the fundamentals-based model produced out-of-sample forecasts that can outperform a random walk model both in the medium and long terms.